The Role of Knee Position in Blood Loss and Enhancement of Recovery after Total Knee Arthroplasty - Cao, Le; Yang, Haitao; Sun, Kai; Wang, Hanbang; Fan, Haitao; Cheng, Wendan (The Journal of Knee Surgery, 2020)
The study aimed to investigate the effects of postoperative position of knee on blood loss and functional recovery after total knee arthroplasty (TKA). We enrolled patients who underwent TKA from 2017 to 2019 in our department with osteoarthritis of the knee in this prospective and randomized study. The patients were randomly allocated to flexion or extension group. In the flexion group, the affected leg was elevated by 30 degrees at the hip and the knee was flexed by 30-degree, postoperatively, while in the extension group, the affected knee was fully extended postoperatively. Patients' data related to postoperative blood loss, Hospital for Special Surgery scores, pain intensity, usage of analgesic drugs, circumference of knee, and range of motion (ROM) of knee were recorded to assess the influence of postoperative leg position on clinical outcomes. Although the transfusion rate was similar between the two groups (p > 0.05), other parameters related to blood loss (including total blood loss, hidden blood loss, usage of analgesic drugs, and postoperative circumference of knee) were significantly lower in the flexion group than those in the extension group (p < 0.05). After 6 weeks and 6 months of rehabilitation, patients gained a similar ROM in the affected knee in both groups (p > 0.05). The length of hospital stay and medical expenses were similar in both groups. Incidence of wound infection and other complications was also similar in both groups (p > 0.05). Elevation of the hip by knee flexion of 30 degrees is an effective and simple method to reduce blood loss after TKA, and contributes to reduction of the dosage of analgesic drugs in the early postoperative period. The routine application of the present protocol also did not increase medical costs and length of hospital stay after TKA.
Keywords: total knee arthroplasty; blood loss; analgesic drugs; position of knee